2012
DOI: 10.4236/as.2012.36103
|View full text |Cite
|
Sign up to set email alerts
|

Seed protein, oil, fatty acids, and minerals concentration as affected by foliar K-glyphosate applications in soybean cultivars

Abstract: Previous studies showed that glyphosate (Gly) may chelate cation nutrients, including potassium (K), which might affect the nutritional status of soybean seed. The objective of this study was to evaluate seed composition (protein, oil, fatty acids, and minerals) as influenced by foliar applications of K + Gly. A greenhouse experiment was conducted at Mississippi Valley State University, using two glyphosate-resistant soybean cultivars DK 4968 and Pioneer 95Y70 grown in a randomized complete block design. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The higher rate of soil application T4 resulted in bigger shifts in linolenic and oleic acid percentages. The decrease in oleic acid is in agreement with our earlier study [25] on foliar application of K and K+glyphosate on soybean seed composition. In contrast, other authors have reported an increase in oleic acid by K fertilizers [26].…”
Section: Seed Protein Oil and Fatty Acidssupporting
confidence: 92%
See 1 more Smart Citation
“…The higher rate of soil application T4 resulted in bigger shifts in linolenic and oleic acid percentages. The decrease in oleic acid is in agreement with our earlier study [25] on foliar application of K and K+glyphosate on soybean seed composition. In contrast, other authors have reported an increase in oleic acid by K fertilizers [26].…”
Section: Seed Protein Oil and Fatty Acidssupporting
confidence: 92%
“…Results showed that leaf and seed mineral concentrations were affected by both foliar and soil application of K. Lower rates of foliar (T1), and soil (T3) applications showed higher concentrations of K, N, and Fe in leaf tissue, with the highest increase of these nutrients found in foliar treatments. Previous studies [11] [23]- [25] reported increased accumulation of N, P, K, and micronutrients in soybean tissues when K fertilizer was applied. In the present study, some of nutrients in seeds responded differently than in the leaves.…”
Section: Leaf and Seed Mineral Concentrationmentioning
confidence: 99%
“…The results showed that all potassium forms induced a remarked promotion in leaf mineral status. Pande et al, (2012) reported increased accumulation of N, P, K, and micronutrients (Fe, Cu, Zn & Mn) in soybean tissues when foliar K fertilizer was applied. Mohsen (2013) who mentioned that applying foliar potassium nitrate on cucumber either alone or combination with humic acid significantly affected leaf NK and chlorophyll contents.…”
Section: -3 Fe Mn Zn and Cu Leaf Contents (Ppm)mentioning
confidence: 99%
“…The data illustrated that all K forms induced observed raise in leaf elements status. Pande et al (2012) demonstrated that increased accumulation of N, P, K, and micronutrients (Mn, Cu, Fe, and Zn) in soybean leaves was obtained when plants sprayed with K fertilizer Mohsen (2013) found that spraying KNO 3 on cucumber either mixture with HA significantly affected leaves chl. and NK contents.…”
Section: Chemical Components (N P K and Carbohydrate%) Of Leavesmentioning
confidence: 99%